Product Scope and Endogenous Fluctuations - Mark Weder; Oscar Pavlov (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Recent empirical evidence suggests that product creation is procyclical and it occurs largely within existing fi rms. Motivated by these findings, the current paper investigates the role of intrafi rm product scope choice in a general equilibrium economy with oligopolistic producers. We show that the multi-product nature of fi rms makes the economy signifi cantly more susceptible to sunspot equilibria. The estimated indeterminate model generates artifi cial business cycles that closely resemble empirically observed fl uctuations.
Keywords: E30; E32; E37; 330